ANALISIS YURIDIS PEMBATALAN PERDAMAIAN DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) (Studi Kasus Putusan Nomor: 376K/Pdt.Sus-Pailit/2017 dan Putusan Nomor: 794K/Pdt.Sus-Pailit/2016) - INDIRA MELISSA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Sunarmi, SH, MHum2. Prof. Dr. Hasim Purba, SH, MHum3. Dr. Dedi Harianto, SH, MHum The research problems formulated based on this case are: 1) What factors can cause the annulment of reconciliation agreement in PKPU process, 2) How about the legal consequence for the debtor if the annulment of the reconciliation agreement is approved or objected, 3) What the basis of the judge’s consideration to settle and pronounce the case in Case No. 376K/Pdt.Sus-Pailit/2017 and Case No. 749K/Pdt-Sus-Pailit/2016. The research applies normative juridical method with descriptive analysis. Library research and field research are done to collect the data by conducting document study and guided interviews. The data are analyzed qualitatively and the conclusion is drwan deductively, from general to specific things. The results of the resaerch demonstrate that the application for an annulment of a reconciliation aggreement, that has been validated by the Judge and approved by creditor and debtor, can be either objected or accepted.Keywords: Reconciliation, Homologa tie, PKPU (Suspension of Debt Payment Obligation)